Health-related quality of life and well-being in people over 75 years of age with end-stage kidney disease managed with dialysis or comprehensive conservative care: a cross-sectional study in the UK and Australia. Issue 5 (19th May 2019) - Shah, Karan K; Murtagh, Fliss E M; McGeechan, Kevin; Crail, Su; Burns, Aine; Tran, Anh D; Morton, Rachael L
Abstract : Objective: To measure health-related quality of life (HRQoL) and well-being in older people with end-stage kidney disease (ESKD) and to determine the association between treatment type and sociodemographic characteristics on these outcome measures. In addition, to assess the convergent validity between the HRQoL and well-being measure and their feasibility and acceptability in this population. Design: Prospective cross-sectional study. Setting: Three renal units in the UK and Australia. Participants: 129 patients with ESKD managed with dialysis or with an estimated glomerular filtration ≤10 mL/min/1.73 m 2 and managed with comprehensive conservative, non-dialytic care. Outcome measures: HRQoL and well-being were assessed using Short-Form six dimensions (SF-6D, 0–1 scale); Kidney Disease Quality of Life (KDQOL-36) (0–100 scale) and Investigating Choice Experiments Capability Measure-Older people (ICECAP-O, 0–1 scale). Linear regression assessed associations between treatment, HRQoL and well-being. Pearson's correlation coefficient assessed convergent validity between instruments. Results: Median age of 81 years (IQR 78–85), 65% males; 83 (64%) were managed with dialysis and 46 (36%) with conservative care. When adjusted for treatment type and sociodemographic variables, those managed on dialysis reported lower mean SF-6D utility (−0.05, 95% CI −0.12 to 0.01); lower KDQOL Physical Component Summary score (−3.17, 95% CI −7.61 to 1.27); lower Mental Component Summary score (−2.41, 95% CI −7.66 to 2.84); lower quality of life due to burden (−28.59, 95% CI −41.77 to −15.42); symptoms (−5.93, 95% CI −14.61 to 2.73) and effects of kidney disease (−16.49, 95% CI −25.98 to −6.99) and lower overall ICECAP-O well-being (−0.07, 95% CI −0.16 to 0.02) than those managed conservatively. Correlation between ICECAP-O well-being and SF-6D utility scores was strong overall, 0.65 (p<0.001), but weak to moderate at domain level. Conclusions: Older people on dialysis report significantly higher burden and effects of kidney disease than those on conservative care. Lower HRQoL and well-being may be associated with dialysis treatment and should inform shared decision-making about treatment options. Trial registration number: UK (IRAS project ID: 134360andREC reference 14/LO/0291) and Australia (R20140203 HREC/14/RAH/36).